2019
DOI: 10.31230/osf.io/sbm8h
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Casting a Wider Net: More Action Needed to Stop Seafood Fraud in the United States

Abstract: Executive SummaryIf you order red snapper at a restaurant, you should get red snapper. If you found out it was something else, you would rightly be angry. But what if you also found out that the fish you ate may have been caught illegally, or had been imported when you thought it was caught locally? Seafood mislabeling can also cover up fish caught or raised with fishing or farming methods that can harm the environment. Overfished species can be labeled as more abundant varieties and cheaper offerings can be s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Firstly, apart from direct fishing, fishing-related activities are restricted to at-sea preparation and transhipment of fish that "have not been previously landed at a port" under Article 2(c). In consequence, a wide variety of illegal operations that occur within the territorial jurisdiction of the market State, such as mislabelling and misrepresentation of species names [47,48], are a priori excluded. Built upon the IUU definition though, the subsidy agreement has considerably trailed behind the IPOA-IUU in raising global awareness of a complementary yet valuable whistle-blower role of market States, which have a more direct bearing on various post-harvest events.…”
Section: Market State Jurisdiction Over the Trade Of Iuu Fishmentioning
confidence: 99%
“…Firstly, apart from direct fishing, fishing-related activities are restricted to at-sea preparation and transhipment of fish that "have not been previously landed at a port" under Article 2(c). In consequence, a wide variety of illegal operations that occur within the territorial jurisdiction of the market State, such as mislabelling and misrepresentation of species names [47,48], are a priori excluded. Built upon the IUU definition though, the subsidy agreement has considerably trailed behind the IPOA-IUU in raising global awareness of a complementary yet valuable whistle-blower role of market States, which have a more direct bearing on various post-harvest events.…”
Section: Market State Jurisdiction Over the Trade Of Iuu Fishmentioning
confidence: 99%
“…A 2019 study found the global average rate of mislabeling to be 8% 46 but regional market studies have reported much higher rates of mislabeling. A report published in 2019 by Oceana 47 looked at over 400 samples in over 25 locations in the United States and found that one in five, or 20%, of the fish were mislabeled. The same technique revealed a 16% mislabeling rate in restaurants in the United States.…”
Section: Trophic Levels and Habitatmentioning
confidence: 99%
“…According to a 2019 study, 21% of seafood is mislabeled in the United States, and 8% is mislabeled worldwide [9,10]. However, mislabeling rates vary enormously among species and seafood types, making generalizations impossible [10].…”
Section: Introductionmentioning
confidence: 99%